PROFIL KOMPETENSI ADAPTASI LINTAS BUDAYA PADA MAHASISWA PESERTA EKSPEDISI KAYAKING PALAPSI UGM KE NEW ZEALAND - Ratri Atmoko Benedictus; Divisi Penelitian dan Pengabdian Masyar (MANASA, 2019)
Globalization makes it easy for a person to cross borders between countries and opens opportunities for interaction and cooperation between cultures. For students, this opportunity opens opportunities to hone intercultural adaptation competencies that are required to be successful in taking part in the global arena. This study aims to obtain an overview of the competency profile of students in adapting to the cultures of other countries. A multi-method approach applied by a variety of data collection, such as questionnaires, interviews, travel journals, and photo documentation of activities. The five participants in this study were Indonesian students who carrying out kayak expeditions in New Zealand. Quantitative data processing in the form of the Paired Group Difference Test showed that there was no significant difference in cross-cultural adaptation competencies among students before and after their expedition to New Zealand. However, the mean comparison test shows an increase in adaptation competence across cultures with dimensions, especially in the Personal Autonomy Dimension. Meanwhile, qualitative data processing shows a high adherence to religious rituals, efforts to maintain original styles in overcoming problems, conformity with new cultures, considering morals and shyness, stereotypes on the environment, stereotypes on facial expressions, and stereotypes of a nation.